Islamisation : comparative perspectives from history - Peacock, A. C. S. (Andrew C. S.) (Edinburgh scholarship online., 2017)
The spread of Islam and the process of Islamisation (meaning both conversion to Islam and the adoption of Muslim culture) is explored in the twenty-four chapters of this volume. Taking a comparative perspective, both the historical trajectory of Islamisation and the methodological problems in its study are addressed, with coverage moving from Africa to China and from the seventh century to the start of the colonial period in 1800. Key questions are addressed. What is meant by Islamisation? How far was the spread of Islam as a religion bound up with the spread of Muslim culture? To what extent are Islamisation and conversion parallel processes? How is Islamisation connected to Arabisation? What role do vernacular Muslim languages play in the promotion of Muslim culture? The broad, comparative perspective allows readers to develop a thorough understanding of the process of Islamisation over eleven centuries of its history.